2020
DOI: 10.5194/hess-24-2399-2020
|View full text |Cite
|
Sign up to set email alerts
|

A novel regional irrigation water productivity model coupling irrigation- and drainage-driven soil hydrology and salinity dynamics and shallow groundwater movement in arid regions in China

Abstract: Abstract. The temporal and spatial distributions of regional irrigation water productivity (RIWP) are crucial for making decisions related to agriculture, especially in arid irrigated areas with complex cropping patterns. Thus, in this study, we developed a new RIWP model for an irrigated agricultural area with complex cropping patterns. The model couples the irrigation- and drainage-driven soil water and salinity dynamics and shallow groundwater movement in order to quantify the temporal and spatial distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The pattern of distribution of groundwater depths (cm) and the direction of its movement for selected months before drainag operations Figure 3 shows the pattern of the distribution of the depths of groundwater and the direction of its movement for the months of March, April, May, June, after drainage operations, as it is noted that the wells close to the vertical drainage are a depth of [5] m. Drainage. While it is noted from the wells far from the tapping basin (1,2,3,13,14,15) the ground water level is still high, meaning that the drainage operation has reduced the groundwater level by about 75% of the total wells , and agrees with the findings of [17] it is noted that the direction of groundwater movement clear from the shapes is heading towards the basin of the tap and the contour lines show the groundwater levels within the study area from the surface of the soil as it is noted that the lowest depth of ground water (120,120,120,120) and the highest depth Ground water (82, 82, 80, 76 for the months of March, April, May and June, respectively). These results are consistent with the findings of [6], who found that the ground water levels have been reduced by the effectiveness of drainage operations.…”
Section: Figuresupporting
confidence: 83%
See 2 more Smart Citations
“…The pattern of distribution of groundwater depths (cm) and the direction of its movement for selected months before drainag operations Figure 3 shows the pattern of the distribution of the depths of groundwater and the direction of its movement for the months of March, April, May, June, after drainage operations, as it is noted that the wells close to the vertical drainage are a depth of [5] m. Drainage. While it is noted from the wells far from the tapping basin (1,2,3,13,14,15) the ground water level is still high, meaning that the drainage operation has reduced the groundwater level by about 75% of the total wells , and agrees with the findings of [17] it is noted that the direction of groundwater movement clear from the shapes is heading towards the basin of the tap and the contour lines show the groundwater levels within the study area from the surface of the soil as it is noted that the lowest depth of ground water (120,120,120,120) and the highest depth Ground water (82, 82, 80, 76 for the months of March, April, May and June, respectively). These results are consistent with the findings of [6], who found that the ground water levels have been reduced by the effectiveness of drainage operations.…”
Section: Figuresupporting
confidence: 83%
“…It was also noted that the amount of dissolved salts has a pattern somewhat similar to the electrical conductivity pattern and is directly proportional [7]. The results also showed a difference in the total dissolved salts values of the drainage waters selected for the summer and winter seasons, as the total dissolved salts values for the summer season were higher than the winter season, and this is due to the increase in temperatures The heat in the summer, which leads to an increase in evaporation rates and the concentration of dissolved salts, and the rain water in the winter season 9 contributes to feeding the groundwater and reducing the concentrations of dissolved salts in it, and this is consistent with [17].…”
Section: Variations In the Total Dissolved Salts (Total Dissolve Salt...supporting
confidence: 72%
See 1 more Smart Citation
“…According to equations ( 1) and ( 4), D * is calculated in (5). It represents the actual sensor placement advantage value.…”
Section: Sensor Target Allocation Modelmentioning
confidence: 99%
“…Moreover, the development of artificial intelligence, cloud computing, and big data has also greatly improved SMWSN efficiency [2][3][4]. However, due to the particularity of soil moisture sensors, the original evaluation mechanism for wireless sensor networks is not well applicable to SMWSNs, so it is urgent to propose a novel network efficiency evaluation mechanism [5].…”
Section: Introductionmentioning
confidence: 99%